Effective Feedback to Improve Students’ Writing Skills - Wulandari, Yasinta (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2022)
Feedback is one of the important elements of teaching and learning which aims to help learners to improve their quality of learning, including in writing activity. This research aims at conducting a library research on how teachers can give their effective feedback in writing classes. Several opinions by experts and previous research related to feedback for writing skills are compiled to provide some strategies that can be used by the teachers for giving effective feedback in writing activity. It is found that by considering the students’ need and purposes of writing, effective feedback that given by teachers can help the learners to know their level of proficiency and their weaknesses. By doing this, students can appreciate their own achievement and fix their weaknesses to make betterment in writing. Teachers can decide which certain kinds of feedback based on the writing purposes and the students’ needs. Therefore, by giving effective feedback, teachers are expected to encourage students’ motivation in improving their writing skills. And it is hoped that the further research will provide in information about oral and written feedback for writing activity.